Association between Weight Change, Health Outcomes, and Mortality in Older Residents in Long-Term Care. Issue 7 (July 2017) - Zhou, Wei; Kozikowski, Andrzej; Pekmezaris, Renee; Lolis, James; Tommasulo, Barbara; Fishbein, Joanna; Wolf-Klein, Gisele
Abstract: Objectives: Despite the numerous health risks associated with being overweight, the effect of weight loss on health and longevity remains controversial, particularly in older adults. We explored the association among weight changes, health outcomes, and mortality in older residents of a skilled nursing facility. Methods: A 6-year retrospective chart review of residents of a long-term care facility was conducted, collecting monthly weights in addition to the clinical and demographic data of all residents for at least 1 year. Weight changes of 5% from baseline month 1 through month 12 were classified as stable, loss, or gain. Demographics, body mass index (BMI), comorbidities, number of hospitalizations, and mortality were analyzed. The association between weight change (and other demographic and clinical variables) and mortality outcomes, as well as number of hospitalizations, was assessed using the χ 2 test, the Fisher exact test, Poisson regression, or negative binomial regression, as appropriate. Results: A total of 116 residents fit inclusion criteria; the median age was 84 years, with 71.6% being women and 88.7% white. The median length of stay was 877.5 days. Median body weight at baseline was 137.3 lb with a BMI of 23.5. More than one-third (36.2%) of residents had stable weight, 37.9% gained weight, and 25.9% lost weight during their stay. Neither weight change category nor baseline BMI was significantly associated with mortality ( P = 0.056 and P = 0.518, respectively). Multivariable models showed that receiving supplementation ( P = 0.04) and having hypertension ( P = 0.04) were significant predictors of mortality after adjusting for the other factors. Losing >5% body weight (compared with maintaining stable weight; P = 0.0097), being a man ( P = 0.0104), receiving a supplement ( P = 0.0171), and being fed by tube ( P = 0.0004) were associated with an increased number of hospitalizations after covariate adjustment. Conclusions: Weight fluctuation and baseline BMI do not appear to be associated with increased risk of death in residents in a skilled nursing facility. Weight loss was associated with an increased number of hospitalizations, however. Abstract : Despite the numerous health risks associated with being overweight, the effect of weight loss on health and longevity remains controversial, particularly in older adults. The primary objective of this study was to investigate the the association between weight change, health outcomes, and mortality in older residents in a skilled nursing facility.